“Vai que a universidade se Trans*Forma”: experiências e epistemologias trans* - Rocha, Késia dos Anjos (2022)
This paper presents some of the results and reflections produced from the research Trans Escrevivências* as a power, developed at the Federal University of Sergipe (UFS) between August 2019 and July 2020. From reports and interviews with trans* students from UFS higher education, we seek to discuss an epistemology about being trans * at the university and how these existences contribute to re-signify the spatial and relational dynamics of that space. The knowledge that comes from the presence of trans * people at the university presents itself as powerful subversion strategies of the binary epistemology that composes it The research adopts a qualitative methodology, which seeks to observe these experiences without the intention of judging them, but taking the way of learning from the differences. We base our analyses on the precepts of gender studies, of transfemist and queer theories and we try to point out some of the potentialities of epistemological productions that emerge from the presence of these subjects, many times understood as subordinates in universities and in society. The occupation of universities by trans people offers us the opportunity to see a more powerful and, therefore, more democratic scenario.